Childhood abuse and neglect and insecure attachment states of mind in adulthood: Prospective, longitudinal evidence from a high-risk sample. (12th April 2017) - Raby, K. Lee; Labella, Madelyn H.; Martin, Jodi; Carlson, Elizabeth A.; Roisman, Glenn I.
Abstract: The present report used data from the Minnesota Longitudinal Study of Risk and Adaptation to investigate the factor structure and childhood abuse and/or neglect related antecedents of adults' attachment states of mind in a high-risk sample. Adult Attachment Interviews (AAIs) were collected when participants were age 26 years ( N = 164) and Current Relationship Interviews (CRIs) were collected from participants ( N = 116) and their romantic partners when target participants were between ages 20 and 28 years ( M = 25.3 years). For both the AAI and the CRI, exploratory factor analyses revealed that (a) attachment state of mind scales loaded on two weakly correlated dimensions reflecting dismissing and preoccupied states of mind and (b) ratings of unresolved discourse loaded on the same factor as indicators of preoccupied states of mind. Experiencing any subtype of abuse and/or neglect, especially during multiple developmental periods, and experiencing multiple subtypes of abuse and/or neglect during childhood were associated with risk for preoccupied (but not dismissing) AAI states of mind regarding childhood relationships with caregivers. Analyses focused on the particular subtypes, and perpetrators indicated that the predictive significance of childhood abuse/neglect for adult's AAI preoccupied states of mind was specific to experiences of abuse (but not neglect) perpetrated by primary caregivers. In addition, experiencing chronic or multiple subtypes of childhood abuse and/or neglect increased risk for dismissing (but not preoccupied) CRI states of mind regarding adult romantic partners.